2021
DOI: 10.3390/ijms22094761
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles of the Rapidly Activated Delayed Rectifier K+ Current in Adult Mouse Heart Primary Pacemaker Activity

Abstract: Robust, spontaneous pacemaker activity originating in the sinoatrial node (SAN) of the heart is essential for cardiovascular function. Anatomical, electrophysiological, and molecular methods as well as mathematical modeling approaches have quite thoroughly characterized the transmembrane fluxes of Na+, K+ and Ca2+ that produce SAN action potentials (AP) and ‘pacemaker depolarizations’ in a number of different in vitro adult mammalian heart preparations. Possible ionic mechanisms that are responsible for SAN pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 86 publications
(131 reference statements)
4
18
0
Order By: Relevance
“…We used a biophysically detailed model of the mouse sinus node action potential: the Hu-Zhang model. 42 In this, we incorporated the observed down-regulation of proteins responsible for the ionic currents I f , I Na , I Ca,L , I Ca,T , I K,r , I K,s , I K,ACh , I NaK , and I GJ (Hcn1, Hcn4, Scn5a, Cacna1c, Cacna1d, Cacna1h, Kcnh2, Kcnq1, Kcnj3, Kcnj5, Atp1a1, Atp1a2, Atp1a3, Cx43) (see Supplementary material online , Figure S6 ). There were no significant changes in the proteins involved in the Ca 2+ clock mechanism of pacemaking (Atp2a2, Ryr2, and Slc8a1), thus these proteins were not considered further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a biophysically detailed model of the mouse sinus node action potential: the Hu-Zhang model. 42 In this, we incorporated the observed down-regulation of proteins responsible for the ionic currents I f , I Na , I Ca,L , I Ca,T , I K,r , I K,s , I K,ACh , I NaK , and I GJ (Hcn1, Hcn4, Scn5a, Cacna1c, Cacna1d, Cacna1h, Kcnh2, Kcnq1, Kcnj3, Kcnj5, Atp1a1, Atp1a2, Atp1a3, Cx43) (see Supplementary material online , Figure S6 ). There were no significant changes in the proteins involved in the Ca 2+ clock mechanism of pacemaking (Atp2a2, Ryr2, and Slc8a1), thus these proteins were not considered further.…”
Section: Resultsmentioning
confidence: 99%
“…To simulate initiation and conduction of pacemaker action potentials, we constructed a one-dimensional model of the sinus node and surrounding atrial muscle ( Figure 2 E ). In the sinus node segment, each node (cell) was modelled by the Hu-Zhang model 42 and in the atrial segments each node (cell) was modelled by equations from Aslanidi et al 43 In the control condition, the action potential was initiated in the centre of the sinus node and conducted to the atrial cells in both directions ( Figure 2 E ). In the HF condition, although the conduction sequence was not changed, both the pacemaker rate and the conduction of the action potential to the atrial muscle were slowed ( Figure 2 F and G ) as observed in humans with HF and in the mouse HF model.…”
Section: Resultsmentioning
confidence: 99%
“…Since activation of I f largely occurs at voltages more negative than the maximal diastolic potential of sinus nodal cells the special importance of I f as the sinus nodal main pacemaker current has even been questioned [46, 47]. In addition, other mechanisms based on calcium handling [48,49,50] or contribution of other ion channels were proposed [51,52,53] to explain cardiac pacemaking in the sinus node. Regardless of the nature of the bradycardia, slower heart rate itself would result in longer APD and enhanced dispersion of repolarization contributing to an increased substrate for arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged QT interval reflects impaired cardiac repolarization that may increase tissue susceptibility to arrhythmogenesis and sudden cardiac death. Acquired LQTS is typically attributable to medications that inhibit the activity of potassium channels encoded by human Ether-à-go-go Related Gene (hERG) [5][6][7]. Congenital LQTS is linked to mutations of proteins that influence cardiac electrogenesis.…”
Section: Introductionmentioning
confidence: 99%